Genetic Evidence Reveals the Indispensable Role of the rseC Gene for Autotrophy and the Importance of a Functional Electron Balance for Nitrate Reduction in Clostridium ljungdahlii - Klask, Christian-Marco; Jäger, Benedikt; Casini, Isabella; Angenent, Largus T.; Molitor, Bastian (Frontiers in Microbiology, 2022)
For Clostridium ljungdahlii, the RNF complex plays a key role for energy conversion from gaseous substrates such as hydrogen and carbon dioxide. In a previous study, a disruption of RNF-complex genes led to the loss of autotrophy, while heterotrophy was still possible via glycolysis. Furthermore, it was shown that the energy limitation during autotrophy could be lifted by nitrate supplementation, which resulted in an elevated cellular growth and ATP yield. Here, we used CRISPR-Cas12a to delete: 1) the RNF complex-encoding gene cluster rnfCDGEAB; 2) the putative RNF regulator gene rseC; and 3) a gene cluster that encodes for a putative nitrate reductase. The deletion of either rnfCDGEAB or rseC resulted in a complete loss of autotrophy, which could be restored by plasmid-based complementation of the deleted genes. We observed a transcriptional repression of the RNF-gene cluster in the rseC-deletion strain during autotrophy and investigated the distribution of the rseC gene among acetogenic bacteria. To examine nitrate reduction and its connection to the RNF complex, we compared autotrophic and heterotrophic growth of our three deletion strains with either ammonium or nitrate. The rnfCDGEAB- and rseC-deletion strains failed to reduce nitrate as a metabolic activity in non-growing cultures during autotrophy but not during heterotrophy. In contrast, the nitrate reductase deletion strain was able to grow in all tested conditions but lost the ability to reduce nitrate. Our findings highlight the important role of the rseC gene for autotrophy, and in addition, contribute to understand the connection of nitrate reduction to energy metabolism.